High-sensitive transmission type of gas sensor based on guided-mode resonance in coupled gratings. Issue 13 (29th July 2018) - Wang, La; Sang, Tian; Li, Junlang; Zhou, Jianyu; Wang, Benxin; Wang, Yueke
Abstract: A new type of high-sensitive transmission gas sensor based on the coupled gratings (CGs) and the corresponding Fabry–Pérot-like (FP-like) model for evaluating the resonance peaks are presented. The estimated locations of the FP-like resonance obtained by this theoretical model are well agreed with those of the exact results. It is shown that a narrow FP-like channel with high transmissivity occurs in the opaque background of the CGs, and its location is shifted linearly with the variation of the refractive index (RI) of the gaseous analyte. The transmission peak of the sideband can be selected as a reference, and it remains nearly fixed as the RI of the analyte is varied. Good sensing properties of the CGs sensor can be maintained, regardless of whether the two grating membranes are laterally aligned or not. The sensitivity of the CGs sensor is immune to the variation of the RI of the substrate. By selecting the higher order FP-like mode ( m = 4), sensitivity as high as 748 nm/RIU with the figure of merit of 374 can be achieved.